PEMBENTUKAN HABITUS BUDAYA AGAMA DI SMA ISLAM SWASTA KABUPATEN BANYUMAS - Muh. Hanif (Jurnal Penelitian Agama, 2013)
This paper discusses the process of forming a habit of religious culture in some islamic private high school in Banyumas Regency, namely: Al Irsyad Al Islamiyah, Muhammadiyah 1 of Purwokerto, and Ma’arif NU of Sokaraja. The planting of a habit of religious culture was practiced by each high school based on its mainstream of religious culture in each school. The planting of religious cultural habits in the schools were applied through: classroom learning process, the development of PAI curriculum, school autonomy, human resources development, outdoor activities. In forming the habits of religious culture in each school, there were some differences of subcultures in each school, and it could be analyzed using curriculum and habits theories, which include habits, field, social capital, and doxa.